Strategi Guru Mentransformasikan Pembelajaran PAI Kurikulum Merdeka (Multi-Situs SMK PGRI 2 dan SMK Al-Huda) - Mohammad Kanzul Fikri; Badrus; Abdul Halim Musthofa (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This research aims to: 1) analyze the implementation of teacher strategies in the transformation of Islamic Religious Education (PAI) learning, 2) evaluate the output of these strategies, and 3) assess the implications of these teacher strategies within the context of the Kurikulum Merdeka (Independent Curriculum). The study employs a qualitative approach with the researcher as the primary instrument, conducting observations, interviews, and documentation directly at the research sites to obtain in-depth and comprehensive data. The subjects are PAI learning practices under the Kurikulum Merdeka at the vocational high school (SMK) level in Kediri City. Key informants include school principals, PAI subject group teachers, and facilitators or mentors involved in the teacher strategies for PAI learning transformation. Data analysis involves data reduction, data presentation, and conclusion drawing. The research was conducted at SMK PGRI 2 and SMK AL-HUDA in Kediri City. The research findings indicate that: 1) Teacher strategies for teaching PAI within the Kurikulum Merdeka at SMK PGRI 2 and SMK AL-HUDA are innovative, flexible, and student-focused. Both schools position teachers as facilitators and emphasize the importance of collaboration, with SMK PGRI 2 focusing on Higher Order Thinking Skills (HOTS) and technology, while SMK AL-HUDA utilizes the jigsaw method and group work. 2) The PAI teacher strategies at both schools successfully build religious character and enhance students' understanding of religion. SMK PGRI 2 integrates religious activities like Dhuha prayers and collaborates with the Lirboyo Islamic Boarding School in project-based learning tailored to students' backgrounds. SMK AL-HUDA emphasizes direct worship practices and the exemplary behavior of teachers in daily activities. 3) The transformation of PAI teacher strategies at SMK PGRI 2 and SMK AL-HUDA improves the quality of learning and religious character in line with the Kurikulum Merdeka. SMK PGRI 2 collaborates with the Lirboyo boarding school and uses the HOTS method to address time constraints and improve students' critical abilities, with teachers actively participating in training. SMK AL-HUDA leverages technology, such as videos of worship practices and religious extracurricular activities, to shape character and social skills. This research contributes to the field of Islamic religious education by providing empirical evidence on the effectiveness of teacher strategies within the Kurikulum Merdeka in an SMK context, specifically through a multi-site study. This study reinforces the understanding that the transformation of PAI learning not only improves academic competence but also prepares students to face socio-cultural challenges